Biology of Kaposi's sarcoma. - Ensoli, Barbara; Sgadari, Cecilia; Barillari, Giovanni; Sirianni, Maria Caterina; Stürzl, Michael; Monini, Paolo (European Journal of Cancer, 2001)
Kaposi's sarcoma (KS) is an angioproliferative disease occurring in several different clinical-epidemiological forms that, however, share the same histological traits and are all associated with infection by the human herpesvirus 8 (HHV8). KS initiates in a context of immune dysregulation characterised by CD8+ T cell activation and the production of Th1-type cytokines that induce a generalised activation of endothelial cells leading to adhesion and tissue extravasation of lympho-monocytes, spindle cell formation and angiogenesis. These phenomena are triggered or enhanced by infection with HHV8 that, in turn, is reactivated by the same cytokines. Productively-infected circulating cells are recruited into 'activated' tissue sites where HHV8 finds an optimal environment for establishing a persistent, latent infection of KS spindle cells (KSC). HHV8 dissemination is favoured by virus escape mechanisms and immune dysregulation, and leads to immune responses that are not effective against the virus but, paradoxically, exacerbates the reactive process. Although early KS is a reactive process of polyclonal nature that can regress, in time it can progress in to a true sarcoma. The progression of KS appears to be due to the deregulated expression of oncogenes and oncosuppressor genes, to the long-lasting expression of the HHV8 latency genes and, for AIDS-KS, is promoted by the proliferative and angiogenic effects of the HIV-1 Tat protein.
Keywords: KS; Spindle cells; Inflammatory cytokines; Angiogenic factors; AIDS; HIV-1 Tat; HHV8; Angiogenesis; bcl-2; Immune evasion